Civil Engineering Program Compliance of SUCs in Western Visayas to Philippine Technological Council – Washington Accord Standards - Paul Erwin S. Sarabia; Ersyl T. Biray (International Journal of Educational Management and Development Studies, 2022)
This descriptive study determined the institutional status of the Bachelor of Science in Civil Engineering (BSCE) program of State Universities and Colleges (SUCs) in Western Visayas in terms of years of implementation, AACCUP level of accreditation, the total number and educational qualification of the faculty, and level of practice of the program to the Philippine Technological Council – Washington Accord (PTC-WA) based on the nine (9) criteria. Data gathered through a survey questionnaire were presented in tabular and narrative presentations and were confirmed through triangulation using comparative analysis and review questions. Results revealed that the majority of the SUCs in Western Visayas had offered the BSCE program for 5-10 years, with Level II accreditation. Most of the faculty members are full-time and have master’s degrees, and the average passing percentage of the graduates in the board examination for the last three years was 75.55% as against the national passing percentage of 41.05%. As an entire group, SUCs in Western Visayas offering the BSCE program had ‘Very Highly Practiced’ the PTC-WA criteria on students and ‘Highly Practiced’ on all the other eight criteria of PTC-WA. As a whole, they had ‘Highly Practiced’ the nine criteria of PTC-WA. Consequently, respondents recommend to the SUCs management to pursue the development of the BSCE program by empowering its heads of units, faculty members, and support staff to cope with the improvement needed in terms of program educational objectives, faculty and support staff, continuous quality improvement, community-oriented programs, and industry-academe linkages.